Pengaruh Gaya Kepemimpinan Transformational dan Lingkungan Kerja Terhadap Kenyaman Kerja Karyawan pada PT. Alluminio Rukan Artha Gading Niaga - Erika Robekca Panjaitan; Ana Ramadhayanti (Ekopedia: Jurnal Ilmiah Ekonomi, 2025)
Job satisfaction is a state in which employees feel safe, comfortable, and free from disturbances while completing their tasks, encompassing both physical environment and social relationships at the workplace. This study aims to analyze employee job satisfaction at PT. Allure Alluminio using a quantitative method. The sampling technique employed is non-probability sampling with a purposive sampling approach, involving 84 respondents. Data were collected through questionnaires and analyzed using validity and reliability tests, multiple linear regression, t-tests, F-tests, and the coefficient of determination (R²) with the assistance of SPSS 25.The results of the t-test indicate that both transformational leadership and work environment have a positive and significant effect on job satisfaction when analyzed separately. The F-test results show that these two variables simultaneously have a significant impact on job satisfaction, with an F calculated value of 205.189, which is greater than the F table value of 3.109, and a significance level of 0.000, which is less than 0.05. The combined effect of both variables accounts for 83.5% of the variance in job satisfaction, while the remaining 16.5% is influenced by other factors outside the scope of this study.